KONDISI SOSIAL EKONOMI DI MASA PANDEMI PADA PEDAGANG KAKI LIMA DI KELURAHAN BANTAN KECAMATAN MEDAN TEMBUNG - Sarah Muthi Nadhirah; Agus Suriadi (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2022)
The influence most felt by street vendors in the Sub District Bantan District. Medan Tembung is the implementation of social distancing policy. As a result, some traders were confused and their income decreased. Social distancing still has an impact on the people's economy. One of the affected community groups is a street vendor in the Sub District Bantan District Convex Field. This study aims to determine the socio-economic conditions of the Street Vendors in Bantan Village, District Tembung fields during the Covid-19 period. The research method used is descriptive qualitative to get a clear picture of the socio-economic conditions of street vendors during the Covid- 19 pandemic. The sampling technique uses accidental sampling, so that data collection can be done through observation and interviews. Based on the research conducted, the results showed that the socio-economic conditions of the street vendors in the Sub District Bantan District. Medan Tembung has a sufficient monthly income level to meet the necessities of life. The level of education that is unable to enter the formal sector. The condition of the housing that is owned is seen from the physical condition of the building and the status of home ownership. Health conditions can be seen from what diseases are complained of and where to seek treatment. The factors that cause street vendors to maintain their business during the Covid-19 pandemic include the necessities of life, low education, inadequate skills, ease of entering the informal sector and having little capital. Other socio- economic impacts for street vendors include the emergence of several street vendors who experience broken household relationships, and disruption of children's education from some street vendors. As for the economic life of street vendors during the covid-19 pandemic, some street vendors chose to increase their income to continue to improve the economy. As well as the income of street vendors during the Covid-19 pandemic decreased very drastically. This is because buyers are quiet, especially those who have regular customers from school children